TINDAK TUTUR IMPERATIF DALAM SLOGAN DAN POSTER TEMA LINGKUNGAN HIDUP DI SEKOLAH SMA ADIWIYATA - Nisa Fitriani; Halimatus Sa’diyah (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
This study has two objectives. (1) Describe the imperative speech acts contained in the slogans and posters at Adiwiyata high school environment, (2) Describe the real form of speech acts imperative in slogans and posters on environmental activities in high school activities Adiwiyata. Data used in the form of text language slogans on banners and posters in the school environment Adiwiyata High School, both located in the room (indoor) and outdoor (outdoor) and interviews to teachers and students. This is a qualitative descriptive study. Data were analyzed using observation, documentation, and interviews. The results of this study were (1) Follow-speech imperatives contained in slogans and posters at the high school environment is imperative sentences Adiwiyata usual, the imperative sentence request, solicitation imperative sentence, errand imperative sentences and imperative sentences restrictions. (2) Analysis of the study of pragmatics related to writing slogan / poster can be concluded that the writing slogan / poster requires creativity and an understanding of the content of the slogan and poster itself, students should be familiar with the characteristics and the type of slogan and poster itself, so that the choice of words persuasive and attractive and easy to understand.